Temporomandibular joint reconstruction with costochondral graft: case series study - Choi, Moon Gi (J Korean Assoc Oral Maxillofac Surg, 2021)
Various techniques have been used to reconstruct the temporomandibular joints, including autogenous transplants and alloplastic implants. Among autogenous grafts, costochondral grafts have mainly been used. A costochondral graft has many advantages over other autogenous grafts and alloplastic implants. Harvest is easy and has minimal impact on patients. The graft can bear functional load well and biocompatibility is excellent. A costochondral graft obviates foreign body reactions and further surgery for revision of alloplastic replacements if the graft takes well. Although long-term prognosis remains unclear, it appears that for autogenous condylar reconstruction, costochondral grafts can be used with few complications and acceptable results. This article describes cases and discusses surgical techniques and considerations related to costochondral grafts.